The relationship between parenting styles, family functioning and mental health among secondary school students in Malaysia - Saw, Jo Anne (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The present study examines whether different types of parenting styles, analyzed separately for mothers and fathers produce better mental health among adolescents. It is hypothesized that maternal and paternal authoritarian parenting style will produce better adolescents' mental health than permissive and authoritative parenting styles. This study also seeks to explore the second hypothesis whereby family functioning will mediate the relationship between parenting styles and adolescents' mental health. A total of 195 Form Four students from two secondary schools around Raub, Pahang were recruited. Respondents answered the Parental Authority Questionnaire (PAQ) for both mother and father, the General Health Questionnaire (GHQ-12) and the General Family Functioning Scale (GF). One-way ANOVA analysis of the data reveals that there is significant difference in the parenting styles for both maternal and paternal parenting in relation to adolescents' mental health. Authoritarian parenting style produces poor adolescents' mental health than permissive and authoritative parenting styles, for both paternal and maternal parenting. The multiple regression analysis reveals that family functioning mediates the relationship between maternal parenting styles and adolescents' mental health but not for paternal parenting styles and adolescents' mental health. In addition, these results suggest the key importance of family process; both parenting styles and family functioning in adolescents' mental health. Limitations of the study and implications for future research are also discussed.